Peran Pabbajita dalam Pelayanan Dhamma kepada Umat Buddha di Kabupaten Tolitoli, Sulawesi Tengah - Leonard, Dhamma Cahyadi; Wardhani, Amita; Herman (STAB Kertarajasa, 2025)
This study aims to identify the role of pabbajita in Dhamma services to the Buddhist community in Tolitoli Regency and its implications on social, economic, and psychological aspects. This research uses a qualitative method with data collection techniques through interviews, observations, and documentation involving 13 respondents. The findings indicate that pabbajita plays a very important role in providing advice, support, and spiritual guidance, which positively impacts the knowledge and understanding of the Buddhist teachings among the community. The research results show that pabbajita offers guidance in meditation practice and Dhamma teachings, which are highly beneficial for the community. Additionally, Pabbajita enhances the community's faith in Buddhist teachings and increases their enthusiasm and participation in religious activities. In conclusion, Pabbajita has a crucial role as a spiritual guide, helping the community improve their mental quality and wisely address daily life challenges. Dhamma services by pabbajita not only strengthen inter-community relationships but also promote tranquility and patience in facing life's challenges, creating a tolerant and harmonious environment in Tolitoli Regency.